Online Closed-Loop Control Using Tactile Feedback Delivered Through Surface and Subdermal Electrotactile Stimulation - Dong, Jian; Jensen, Winnie; Geng, Bo; Kamavuako, Ernest Nlandu; Dosen, Strahinja (Frontiers in Neuroscience, 2021)
Limb loss is a dramatic event with a devastating impact on a person’s quality of life. Prostheses have been used to restore lost motor abilities and cosmetic appearance. Closing the loop between the prosthesis and the amputee by providing somatosensory feedback to the user might improve the performance, confidence of the amputee, and embodiment of the prosthesis. Recently, a minimally invasive method, in which the electrodes are placed subdermally, was presented and psychometrically evaluated. The present study aimed to assess the quality of online control with subdermal stimulation and to compare it to that achieved using surface stimulation (common benchmark) as well as the impact of training on the two modalities. Methods: Ten able-bodied subjects performed a PC-based compensatory tracking task. The subjects employed a joystick to track a predefined pseudorandom trajectory using feedback on the momentary tracking error, which was conveyed via surface and subdermal electrotactile stimulation. The tracking performance was evaluated using the correlation coefficient (CORR), root mean square error (RMSE), and time delay (TD) between reference and generated trajectories. Results: Both stimulation modalities resulted in good closed-loop control, and surface stimulation outperformed the subdermal approach. There was significant difference in CORR (86 % vs 77 %) and RMSE (0.23 vs 0.31) between surface and subdermal stimulation (all p < 0.05). The RMSE of the subdermal stimulation decreased significantly in the first few trials. Conclusion: Subdermal stimulation is a viable method to provide tactile feedback. The quality of online control is however somewhat worse compared to surface stimulation. Nevertheless, due to minimal invasiveness, compactness, and power efficiency, it could be an attractive solution for the functional application in sensate prostheses.